Dana Talangan Haji (Fatwa DSN dan Praktek di LKS) - Syamsul Hadi; Widyarini Widyarini (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2011)
Based on DSN-MUI fatwa, some Islamic Finance Institutions (LKS) offer Hajj Credit (Dana Talangan Haji). This product helps moslem to register for the forthcoming hajj session. DSN-MUI fatwa forced LKS to use al-Qardh contract for this product and not related LKS ujrah to the ammount of Hajj Credit. The problem is does this hajj credit product really sharie based on shariah? This research resulted that Ujrah revenue was based on Qardh Fund that was not allowed by DSN Fatwa. DSN-MUI should revised its fatwa to terat equaly between LKS and Jamaah. DSN-MUI and LKS suggested to take use akad al-Ijarah muntahiya bittamlik with sale and lease back concept.